2016
DOI: 10.1177/1460458215598636
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of SMS text messaging in a prostate cancer educational intervention for African American men

Abstract: African Americans' greater access to mobile phones makes short messaging service technology a promising complement to health promotion interventions. Short messaging service text messages were added to the Men's Prostate Awareness Church Training project, a men's health intervention for African American men. We report on the feasibility and acceptability of the use of short messaging service text messages in the intervention. Short messaging service text messages served as (1) workshop reminders; (2) post-work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Messages were sent at 9 am so participants could read them throughout the day. 22 Recruitment. We enrolled participants in the messaging component during baseline data collection at each church to reduce sign-up burden on participants.…”
Section: Intervention Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Messages were sent at 9 am so participants could read them throughout the day. 22 Recruitment. We enrolled participants in the messaging component during baseline data collection at each church to reduce sign-up burden on participants.…”
Section: Intervention Descriptionmentioning
confidence: 99%
“…Another study described the successful integration of a mobile messaging component into a multi-level, church-based program; however, the study focused on prostate cancer prevention. 22 To the best of our knowledge, there are no prior published articles that examine mobile messaging as part of a multi-level, faith-based program to impact dietary and physical activity behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a group of healthy African-American men who received a prostate cancer educational intervention consisting of short text messages related to prostate cancer awareness, Le and colleagues [99] found that 65% of the participants wished to continue receiving text messages pertaining to workshop reminders, post-workshop reinforcement, spiritual/motivational messages, and retention after completing the study. However, more than one-third of the study participants did not recall receiving the text messages.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Features that participants were interested in seeing with respect to text messages were personalized messages, content that was relevant to them, and messages that were positive and reassuring. Conversely, participants did not want to receive test results or bad 17 news via text messages, or content that included shorthand phrases or required complex replies.In a group of healthy African-American men who received a prostate cancer educational intervention consisting of short text messages related to prostate cancer awareness, Le and colleagues [99] found that 65% of the participants wished to continue receiving text messages pertaining to workshop reminders, post-workshop reinforcement, spiritual/motivational messages, and retention after completing the study. However, more than one-third of the study participants did not recall receiving the text messages.…”
mentioning
confidence: 99%